2017
DOI: 10.1016/j.jaci.2016.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in B-cell subsets in pediatric patients with early atopic dermatitis

Abstract: Peripheral B and T cells are altered in pediatric patients with early AD, but T cells predominate in skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 73 publications
2
44
0
Order By: Relevance
“…55 In a subsequent study by the same group using the same patient population, disproportionally higher T-cell than B-cell counts were found in skin lesions of pediatric patients compared to adult patients with AD. 109 Data from these studies suggest that Th2 activation plays a more important role in children with AD, and that Th1 and Th22 activation may be influenced by immune development and disease chronicity. This may suggest that the presence of Th2 high clusters might be even more pronounced in paediatric AD than in adult AD.…”
Section: Heterogeneity In Children With Atopic Dermatitismentioning
confidence: 97%
“…55 In a subsequent study by the same group using the same patient population, disproportionally higher T-cell than B-cell counts were found in skin lesions of pediatric patients compared to adult patients with AD. 109 Data from these studies suggest that Th2 activation plays a more important role in children with AD, and that Th1 and Th22 activation may be influenced by immune development and disease chronicity. This may suggest that the presence of Th2 high clusters might be even more pronounced in paediatric AD than in adult AD.…”
Section: Heterogeneity In Children With Atopic Dermatitismentioning
confidence: 97%
“…In addition, latter studies revealed an altered B cell distribution in AD with elevated transitional B cells, IgE expressing memory B cell subsets and plasmablasts; moreover, an elegant work with ovalbuminsensitized CD19-deficient mice shed light on the role of B cells in the pathogenesis of AD [9,46]. In another study, low numbers of non-switched memory B cells were showed in paediatric AD compared to adult AD confirming the dominance of T-cell dependent mechanisms in early childhood [38]. Aforementioned evidences suggest that upon secondary antigen exposure and activation in inflammatory environment, circulating memory TFH cells could migrate to draining lymphoid nodes and gain fully matured effector TFH phenotype to support GC responses [47,48].…”
Section: Discussionmentioning
confidence: 92%
“…Early AD is often associated with other allergic diseases, including food allergy, allergic bronchial asthma as well as allergic rhinoconjunctivitis and from childhood this sequential disease development is called the atopic march [37]. Atopy has the aptitude to develop heightened IgE levels since T cell-B cell interactions seem to associate with this phase [38]. Most studies investigated immune-competent cells in cohort of children as well as adults did not compare the results simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the help of interleukin‐4 (IL‐4) and/or IL‐13 produced from type 2 helper T (Th2) cells, activated B cells produce IgE . The diverse activation and differentiation of multiple B‐cell subsets with significant correlation with circulating IgE levels have been reported in AD but not in psoriasis or normal controls . Consistent with preponderant Th2 deviation in early childhood AD, elevated levels of total or allergen‐specific IgE have been noted in infantile and early childhood AD .…”
Section: Introductionmentioning
confidence: 99%